(untitled) (Conferencea, 2022)
Nowadays to learn foreign languages is very important in the world and in our country too, especially to learn English is very popular in our country among young’s. One of the important issues in educational sphere in Uzbekistan is to raise the quality of teaching education, especially teaching foreign languages in primary and secondary special education